2001
DOI: 10.1056/nejm200103083441002
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Embryonic Dopamine Neurons for Severe Parkinson's Disease

Abstract: Human embryonic dopamine-neuron transplants survive in patients with severe Parkinson's disease and result in some clinical benefit in younger but not in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,642
8
40

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,204 publications
(1,714 citation statements)
references
References 24 publications
24
1,642
8
40
Order By: Relevance
“…Some parkinsonian patients that received fetal VM grafts in recent clinical trials developed off-medication dyskinesias or graft-induced dyskinesias (GID) (Freed et al, 2001;Hagell et al, 2002;Olanow et al, 2003). The proportion of patients in these 3 studies with GID severe enough to constitute clinical therapeutic problems has been estimated to be between 7 and 15% (Hagell and Cenci, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some parkinsonian patients that received fetal VM grafts in recent clinical trials developed off-medication dyskinesias or graft-induced dyskinesias (GID) (Freed et al, 2001;Hagell et al, 2002;Olanow et al, 2003). The proportion of patients in these 3 studies with GID severe enough to constitute clinical therapeutic problems has been estimated to be between 7 and 15% (Hagell and Cenci, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies in the rodent (reviewed by Brundin et al, 1994), and in the primate (Annett, 1994;Bankiewicz et al, 1993;Elsworth et al, 1996;Fine et al, 1988;Taylor et al, 1991) have shown that grafts of fetal DA neurons can lead to reversals in biochemical and behavioral indices of DA deficiency. However, in clinical studies the improvements in Parkinsonism have been variable, and generally rather modest (Freed et al, 1992;Freed et al, 2001;Lindvall and Hagell, 2001;Olanow et al, 2003;Redmond, 2002;Spencer et al, 1992;Widner et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Guyuron and colleagues used a skin incision to expose superficial nerves and muscles, which were cut during the active surgery but, in the placebo group, the integrity of these structures was maintained 33 . Trials investigating transplantation of dopaminergic neurones as a treatment for Parkinson’s disease not only required skin incision but also burr holes in the skull 34, 35 .…”
Section: Strategies Used To Maintain Blinding In Interventional Placementioning
confidence: 99%
“…Interventional treatment often requires additional procedures, such as diagnostic scans or medication to prevent infection 43, 56, 62 , blood clots 40 , transplant rejection 63 , or epileptic fits 35 . For example, in the trial by Freed and colleagues, both groups received identical preoperative evaluation, intraoperative sedation and pain control, underwent two PET scans and a MRI scan, and received phenytoin 35 .…”
Section: Strategies Used To Maintain Blinding In Interventional Placementioning
confidence: 99%
See 1 more Smart Citation